2015
DOI: 10.1007/s13277-015-3600-2
|View full text |Cite
|
Sign up to set email alerts
|

Expressions of miR-181a and miR-20a in RPMI8226 cell line and their potential as biomarkers for multiple myeloma

Abstract: Multiple myeloma (MM) is characterized by clonal proliferation of malignant plasma cells in the bone marrow. The anti-tumor activity of bortezomib (a proteosome inhibitor) in MM is challenged by emergence of drug resistance. MicroRNAs (miR) regulate and orchestrate multiple cellular pathways. We investigate the contribution miR-181a and miR-20a expressions' on cell proliferation and apoptosis in RPMI8226 cell line and their influence on bortezomib treatment. RNA isolation, quantitative real-time PCR (qRT-PCR),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 30 publications
1
11
1
Order By: Relevance
“…In the present study, the expression levels of miR-181a were significantly increased in BM samples from patients recently diagnosed with MM and in the MM RPMI8226 cell line compared with normal plasma cells, which was consistent with the results from previous studies (10,13,25). In the present study, upregulation of miR-181a was associated with disease stage, suggesting its potential contribution to the progression of MM.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, the expression levels of miR-181a were significantly increased in BM samples from patients recently diagnosed with MM and in the MM RPMI8226 cell line compared with normal plasma cells, which was consistent with the results from previous studies (10,13,25). In the present study, upregulation of miR-181a was associated with disease stage, suggesting its potential contribution to the progression of MM.…”
Section: Discussionsupporting
confidence: 92%
“…miR-181a was the first miRNA reported to serve a regulatory role in B cell differentiation in the bone marrow (BM), and ectopic expression in hematopoietic stem/progenitor cells promoted a substantial increase in the generation of B cells, both in vitro and in vivo (12). Previous data have revealed that miR-181a is a biomarker of MM and regulates the progression of MM (13,14). In a number of different types of tumor, miR-181a was involved in the regulation of tumor proliferative, migratory and invasive abilities, thereby highlighting its potential as a prognostic factor and therapeutic target (15).…”
Section: Introductionmentioning
confidence: 99%
“…Several members of the miR-17-92 cluster regulate cell proliferation. For example, miR-17-5p promoted cell proliferation in gastric 39 and colorectal cancer cell lines 40 , and miR-20a promoted cell proliferation in human lung cancer 41 and multiple myeloma 42 . In the present study, we demonstrated that the miR-17-92 cluster promotes chicken cell proliferation through its two members, miR-17-5p and miR-20a (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…miR-20a has an important in various human cancers, including gastric cancer (15), colorectal cancer (16), non-small cell lung cancer (17) and cervical cancer (18). Importantly, significant expression of miR-20 has been found in myeloma (19,20). Several studies have suggested that the dysregulation of miRNAs initiates the activation of the phosphatase and tensin homolog (PTEN)/phosphoinositide 3-kinase (PI3K)/protein kinase B (Akt) signaling pathway,…”
Section: Introductionmentioning
confidence: 99%